A farewell to arms - Hemingway, Ernest, 1899-1961. (New York : Scribner Paperback Fiction, 1995)
An American ambulance driver serving on the Austro-Italian front in World War I becomes entangled with an English nurse and deserts to join her after the retreat of Caparetto.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Wilson's Senior High School.
8.6
Adult
Keywords: Man-woman relationships -- Fiction; World War, 1914-1918 -- Fiction; Man-woman relationship -- Fiction; War stories; World War, 1914-1918 -- Fiction; War stories